Pemanfaatan Framework Codeigniter Dalam Pembuatan Sistem Informasi Bimbel Bahasa Inggris Berbasis Web - Weiskhy Steven Dharmawan; Ardiyansyah Ardiyansyah (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
The Pontianak English Village Tutoring Center is one of the institutions engaged in English education. The system applied still uses book media for recapitulation or report presentation. The problem that becomes an obstacle for the English village is that the admin who processes the data often makes mistakes and delays in recording and making reports. Therefore, this study describes the creation of a web-based English tutoring information system using the Codeigniter framework in assisting the required information system. In addition, in this study the author uses a descriptive method and the waterfall model. This information system consists of three users, namely: admin, student, and owner. Where the admin can manage all menu data consisting of registration confirmation, student payments, schedule input, classes. Students register, pay, and re-register. While the owner sees the report data that has been inputted. This web-based tutoring information system is expected to help Pontianak English Village in recording all existing activities and students who want to register do not need to bother coming to the place, only using mobile phones can register and make payment transactions using the website